Extent and prevalence of post-exercise and nocturnal hypoglycemia following peri-exercise bolus insulin adjustments in individuals with type 1 diabetes - Olivia McCarthy (Nutrition, Metabolism and Cardiovascular Diseases, 2021)
To detail the extent and prevalence of post-exercise and nocturnal hypoglycemia following peri-exercise bolus insulin dose adjustments in individuals with type 1 diabetes (T1D) using multiple daily injections of insulins aspart (IAsp) and degludec (IDeg).